Audit Sistem Informasi Pemerintahan Daerah (Sipd) Penatausahaan Pada Kantor Samsat Kelapa Dua Tangerang Menggunakan Framework Cobit 5 - Shinta Nuriyah; Sigit Auliana; Eris Dwi Purnama (Universitas Pakuan, 2025)
AUDIT OF THE REGIONAL GOVERNMENT INFORMATION SYSTEM ADMINISTRATION AT THE SAMSAT KELAPA DUA TANGERANG OFFICE USING THE COBIT 5 FRAMEWORK This research aims to audit the Regional Government Information System (SIPD) Administration at the SAMSAT Kelapa Dua Tangerang Office using the COBIT 5 framework. The main objective is to evaluate system performance, identify potential problems, and provide recommendations for improvement to enhance the effectiveness and efficiency of Administration governance at the office. The research method was conducted through direct observation, interviews with relevant parties, and analysis of primary and secondary data. The results show that several processes for IT human resource management (APO07), risk management (APO12), and IT service operations (DSS01) are still not fully documented, standardized, or systematically managed. The average capability level is between 1 and 2, indicating that processes are only performed without formal controls. Based on these results, it is recommended that the SAMSAT Kelapa Dua Tangerang office improve IT process documentation and standardization, strengthen employee training, and implement stricter monitoring and evaluation systems to achieve higher capability levels.